NIH Tobacco Research and the Emergence of Tobacco Regulatory Science. Issue 4 (8th October 2021) - Meissner, Helen I; Sharma, Kriti; Mandal, Rachel J; Garcia-Cazarin, Mary; Wanke, Kay L; Moyer, Jonathan; Liggins, Charlene
Abstract: Introduction: This study explores how the emergence of FDA-funded Tobacco Regulatory Science (TRS) research complements and perhaps influenced the direction of tobacco research supported by NIH. Aims and Methods: New NIH- and FDA-funded tobacco projects awarded in fiscal years (FY) 2011–2020 were identified using internal NIH databases of awarded grants. Project abstracts and research aims were coded by the authors to characterize research domains and tobacco products studied. Results: Between FY 2011 and 2020, NIH funded 1032 and FDA funded 322 new tobacco projects. For the years and grant activity codes studied, the number of new NIH tobacco projects declined while FDA's increased; combined the number of new projects held steady. Much of NIH research included smoking combustibles (43.7%). The most common products in FDA research were cigarettes (74.8%) and e-cigarettes/ENDS (48.1%). Most NIH (58.6%) and FDA (67.7%) projects included research on the determinants of tobacco use. Another area of apparent overlap was health effects (29.5% NIH and 30.1% FDA). Projects unique to NIH included treatment interventions (33.3%), disease pathology/progression (17.8%) and neurobiology (18.9%). A minority of both NIH and FDA projects included populations particularly vulnerable to tobacco product use. Conclusions: In total, support for new tobacco research supported by NIH and FDA combined remained steady for the time period covered, though there was a concomitant decline in NIH tobacco projects with the increase in FDA-funded TRS projects for the activity codes studied. Despite the apparent overlap in some areas, both NIH and FDA support research that is unique to their respective missions. Implications: NIH continues to support tobacco research that falls within and outside of FDA's regulatory authorities. This research still is needed not only to bolster the evidence base for regulatory decisions at the national and state levels, but also to advance a comprehensive scientific agenda that can inform multiple levels of influence on tobacco control, use and addiction. It will be important to continue monitoring FDA-funded TRS and NIH-funded tobacco research portfolios to ensure that the level of support for and focus of the research is sufficient to address the burden of tobacco-related morbidity and mortality.